IMPLEMENTASI PERAN KEPALA SEKOLAH DALAM MENGEMBANGKAN KINERJA GURU - ASTUTI Astuti (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstrak. Schools are formal educational institutions that have specific directions and goals, their achievements certainly require unification and mobilization to achieve goals. Therefore, principals as leaders of educational institutions have great responsibilities, both as leaders, managers, administrators, and motivators. School integrity is characterized by the realization of an effective learning process. The effectiveness of learning is largely determined by the teacher because the teacher as a leading curriculum translator. Therefore, it is hoped that the principal will carry out his role as a leader, manager, administrator, and motivator for the teacher so that the teacher can improve his performance. Teacher performance can be measured by work behavior and work results and ownership competencies that have been required as teachers.